Knowledge of Dental Interns towards Emergency Management of Avulsed Tooth in Dental Colleges in Nepal - Limbu, S; Dikshit, P; Bhagat, T; Mehata, S (Journal of Nepal Health Research Council, 2014)
Background: Avulsion is most common traumatic injury of tooth. Adequate knowledge about management of this situation can save a tooth. This study was conducted to investigate the knowledge and attitude of dental interns of Nepal in the management of tooth avulsion and also evaluate the need for further education on managing avulsed teeth.Methods: A cross-sectional survey consisting of 18 items were filled, collected and mailed back by 121 interns of Nepal from five dental colleges. The study period was from July to September 2013. All returned questionnaires were analyzed using SPSS 17.0.Â Results: Dental interns with more efficient in answering questions regarding- ideal time for replantation of an avulsed tooth (p=0.024), splinting period (p=0.008), the critical factor in the outcome of replanted tooth (p=0.010) and the better prognosis with open apex (p=0.001). Prior knowledge about management of avulsed tooth had a role in correctly answering questions on type of splint used (p=0.022) and better prognosis with open apex (p=0.018). Attending educational program on trauma management helped them in correctly answering questions on avulsed permanent tooth to be replanted (p=0.043) and the type of splint used (p=0.014).Conclusions: Dental interns experience, prior knowledge and educational programs with dental management regarding traumatic injuries scored significantly higher than without such training or acquired information. However further knowledge needs to be enhanced by continued educational programs to ensure appropriate treatment.Â Keywords: avulsion; emergency management; replantation; storage media; splinting time.